In vivo evaluation of stem cell aggregates on osteochondral regeneration. Issue 8 (11th November 2016) - Sridharan, BanuPriya; Laflin, Amy D.; Holtz, Michael A.; Pacicca, Donna M.; Wischmeier, Nicholas K.; Detamore, Michael S.
ABSTRACT: To date, many osteochondral regenerative approaches have utilized varied combinations of biocompatible materials and cells to engineer cartilage. Even in cell‐based approaches, to date, no study has utilized stem cell aggregates alone for regenerating articular cartilage. Thus, the purpose of this study was to evaluate the performance of a novel stem cell‐based aggregate approach in a fibrin carrier to regenerate osteochondral defects in the Sprague‐Dawley rat trochlear groove model. Two different densities of rat bone marrow mesenchymal stem cell (rBMSC) aggregates were fabricated by the hanging drop technique. At 8 weeks, the cell aggregates supported the defects and served as a catalyst for neo‐cartilage synthesis, and the experimental groups may have been beneficial for bone and cartilage regeneration compared to the fibrin‐only control and sham groups, as evidenced by histological assessment. The cell density of rBMSC aggregates may thus directly impact chondrogenesis. The usage of cell aggregates with fibrin as a cell‐based technology is a promising and translational new treatment strategy for repair of cartilage defects. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1606–1616, 2017.